STUDI KASUS TENTANG SISWI MINDER DALAM PERGAULAN PADA KELAS VIII SMP NEGERI 1 SEMPARUK - Fetriana, Shara; Yuline, Yuline; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â Abstract The research entitled case study of female students in social interaction in class VIII SMP Negeri 1 semparuk. The general problem of this research is how to help the minder student in socializing in class VIII SMP N 1 SEMPARUK. while the goal is to get the factors causing, the relief efforts and the results obtained after being given guidance on the female minder in the association. The approach used is qualitative approach using descriptive method and case study research form. There are two case subjects in this study. alternative assistance given is Behavioral is a form of treatment by using systematic desentisation techniques, assertive therapy, impolsif therapy and operan conditioning techniques so that the behavior of the subject can be better. While the second aid uses directive techniques and didactic techniques in the RET counseling model so that case subjects can change the irrational mindset into a rational mindset.Keywords: Case Study, Schoolgirl, Inferiority Feeling